Dr. Jeffrey Raval — Deep Plane Facelift — Denver - Raval, Jeffrey (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Jeffrey Raval, practicing in Denver, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003034; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; denver